Handling of grievances in the South African Police Service: a case of Pretoria Policing Area - Hlongwane, Paulus (My University, 2023)
Over the years, the South African Police Service (SAPS) has been recording the highest number of employee grievances in comparison to other government institutions in South Africa. Some of the grievances reported by employees remain unresolved. For these reasons, the primary aim of this study was to determine the causes of the high rate of grievances in the Pretoria policing area of the SAPS. To achieve the primary aim of the study, concurrent mixed methods were applied, in particular the survey questionnaire, interviews and document study. On the one hand, the SPSS version 26 software was used to analyse quantitative data collected through a survey questionnaire. On the other hand, qualitative content analysis was used to analyse data collected through interviews. The findings of this study illustrate that the common sources of grievances in the SAPS are promotions, unpaid leave, unfair treatment and rejection of application for transfers. The findings of this study confirmed that autocratic supervisory behaviour as a management factor is among the major factors that account for the high rate of grievances in the SAPS. The study has found that in the process of applying the grievance procedure to address grievances, the SAPS complied with timelines linked to each grievance phase only to a slight extent. In relation to the causes of unresolved grievances, the study found that the involvement of legal representatives in grievances, lack of impartiality of the part of grievance officers, the grievants’ failure to provide testimony and failure to gather adequate evidence pertaining to grievances contributed to the high rate of unresolved grievances. This study has, however, concluded that despite the challenges experienced in grievance handling, the SAPS has the capacity and resources to turn the situation around thereby ameliorating the current situation pertaining to grievances.
Thesis (Ph.D. (Public Administration)) -- University of Limpopo, 2023
Keywords: Grievance; Grievance arbitration; Grievance handling; Grievance mediation; Grievant; Grievance procedures; Grievance arbitration -- South Africa; Police